The Use of Mother Tongue in General English Program for Teenagers in the Second and Fourth Levels - Katherine Olga Bawono; Julia Eka Rini (Institute of Research and Community Outreach - Petra Christian University, 2014)
This study reports the teacher’s use of mother tongue (Bahasa Indonesia) in English as Foreign Language (EFL) classroom in Indonesia. The study was conducted in an English language course for teenagers, and focused more in the second and fourth level. It was revealed that beside English language, Bahasa Indonesia was used by the teachers as the medium of instruction for some functions: conveying and checking the meaning of words/sentences, explaining grammar, organizing tasks, maintaining discipline, and gaining contact with individual student; and the teachers’ reason in using Bahasa Indonesia was to make sure that the students understand about what they delivered. In addition, some similarities and differences were found in the comparison of the second and fourth levels.